Comunidade de formigas (Hymenoptera: Formicidae) de áreas urbanas da região oeste de Santa Catarina, Brasil - Lutinski, Junir Antonio (2014)
Urbanization process is a major threat to biodiversity, and among organisms found in urban areas, ants represent an important but understudied group compared to other insects. Knowing the richness and composition of the ant fauna inhabiting urban areas and the factors exerting pressure on these communities are imperative for the development of management and conservation plans. This study presents a survey of the ant fauna found in ten urban areas of southern Atlantic Forest biome and describes the changes in richness, abundance and species composition among four types of environments along a gradient of intensification of human activities. It also presents information about the temporal and microclimate influence (luminosity, temperature, relative humidity and wind speed) on ant assemblages. Sampling was conducted in forest fragments, green areas, schools and recycling centers. Two complete sets of samplings were performed in 2011, in the summer (February and March) and spring (October and November). Sardine and glucose baits, and manual collection were used as sampling techniques. Ant assemblages of each city were evaluated and compared by rarefaction analysis and richness estimates. The ant community structure was described from a Nestedness test (NODF) and an Indicator Species Analysis (ISA). The temporal effect on the abundance and composition of the assemblages was verified through an NMDS ordination (Non-Metric Multidimensional Scaling). Canonical Correspondence Analysis (CCA) was employed to determine the microclimate effect on the assemblages. We registered 8,790 occurrences of ants, and identified 140 species of 37 genera, 19 tribes and nine subfamilies. Three of these species, Gnamptogenys sulcata (Smith, 1858), Camponotus personatus Emery, 1894 and Solenopsis invicta Buren, 1972 were recorded for the first time in the Santa Catarina state. Exclusive species were found in nine cities, indicating variation in species composition from one city to another. A nesting pattern was observed along the gradient, i.e. the assemblages belonging to environments under greater human pressure are subsets of the ant fauna of more preserved environments. Forest fragments presented the highest number of indicator species (12), followed by green areas (4) and schools (3). The sampling conducted in spring (October and November) resulted in a 20% greater richness (S = 132) compared to samples collected in summer (February and March) (S = 104). The luminosity and relative humidity were the most prevalent microclimatic variables that influenced the assemblages of ants in the three types of environments and in the two sampling periods. These results expand our understanding of the factors that control the activity of ants in urban environments and provide subsidies for the implementation of policies for urban development and conservation plans.